Regulation of gut microbiome by ketogenic diet in neurodegenerative diseases: A molecular crosstalk - Kaviyarasan, Shobana; Chung Sia, Edmund Lee; Retinasamy, Thaarvena; Arulsamy, Alina; Shaikh, Mohd Farooq (Frontiers in Aging Neuroscience, 2022)
The gut taxonomical profile is one of the contributory factors in maintaining homeostasis within the central nervous system (CNS). Of late, the efficacy of diet as a target of treatment, and how various dietary interventions may modulate gut microbiota differently have been an area of focus in research. The role of ketogenic diet (KD) in particular has been well-established in other diseases like intractable epilepsy due to its postulated effects on gut microbiome modulation, resulting in neuronal stability and prevention of epileptogenesis. Therefore, this systematic review aimed to critically evaluate the current available literature investigating the interplay between the three distinct entities: ketogenic diet, neurodegeneration, and gut microbiota, which may serve as a focus guide for future neurodegenerative diseases (ND) therapeutic research. A comprehensive literature search was performed on three databases; PubMed, Scopus, and Ovid Medline. A total of 12 articles were selected for critical appraisal, after subjecting to the inclusion and exclusion criteria in this study. The selected articles revealed that the hopes of KD as a treatment modality for ND are being ventured into as these individuals are said to acquire gut dysbiosis, primarily through increased colonization of phyla Proteobacteria and Firmicutes. Although positive effects including restoration of healthy gut microbes such as Akkermansia Muciphilia sp., improvement in cognitive functioning and decline in neuro-inflammatory markers were noted, this systematic review also depicted conflicting results such as decrease in alpha and beta species diversity as well as diminution of healthy gut commensals such as Bifidobacteriace. In addition, positive neuromodulation were also observed, notably an increase in cerebral blood perfusion to ventromedial hippocampal region via increased expression of eNOS and clearance of amyloid-beta proteins across the blood-brain-barrier via expression of p-glycoprotein. Neuroprotective mechanisms of ketogenic diet also included downregulation of mTOR expression, to prevention acceleration of pathological diseases such as Alzheimer's. Thus due to this conflicting/contrasting results demonstrated by ketogenic diet, such as a decline in gut species richness, diminution in beneficial microbes and decline cognition unless delivered in an intermittent fasting pattern, further studies may still be required before prior recommendation of a ketogenic diet therapeutic regime in ND patients.